Fast neutron detectors and portal monitors based on solid-state heavy-oxide scintillators. (October 2017) - Ryzhikov, V.D.; Naydenov, S.V.; Piven, L.A.; Onyshchenko, G.M.; Smith, C.F.; Pochet, T.
Abstract: We have developed and fabricated large-sized scintillation blocks for detection of fast neutrons based on the heavy-oxide single crystals СWO, ZWO, BGO (diameter 40–50 mm, length 80–100 mm). These crystals demonstrate fast neutron detection efficiencies of not less than 50% without using an external plastic moderator. Based on these new detectors, we have created an experimental prototype of a portal monitor to detect mixed neutron/gamma radiation. The measured sensitivity for fast neutron detection was equal to or better than that of traditional 3 Не gas discharge counters, with weight and size being lower by as much as an order of magnitude. It can be expected that this will also result in reduced production and operational costs. The interaction of fast neutrons with the heavy oxide scintillators was studied, and the respective contributions of the mechanisms of inelastic scattering of fast neutrons, resonance scattering of intermediate neutrons, and radiative capture of slow neutrons were determined. We have also developed an improved spectrometric "3-windows" method for separate detection of fast neutrons against the background of gamma-radiation.